Social insects: Morphophysiology of the nervous system - Nocelli, Roberta C.F.; Roat, Thaisa C. [UNESP]; Zacarin, Elaine C.M. Silva; Palma, Mario Sérgio [UNESP]; Malaspina, Osmar [UNESP] (My University, 2011)
Social insects are an interesting model to neurobiological studies due to the simplicity of its brain commanding the complex behaviors demanded by eusocial relationships and its capacity of learning and memorizing. In their social structure, usually have differentiated sex and caste, where individuals have different morphology, physiology and behavioral patterns correlated with their functions in the society and represented by some brain polymorphism. They have a rich behavioral repertoire and perform various tasks throughout their lives that involve a complex and diverse system of learning. The brain is the main center of association of the insect. Receives sensory impulses coming from the sense organs of the head and from the ventral ganglia nerve chain, through ascending interneurons. Orders emanating from the brain to the antennae muscles and the posterior part of the body, passing through the descending pathways, pre-motor, going to the ganglia of the ventral nerve chain. In addition, the brain is the center of the integration of activities, which produce organized patterns of long-term behavior driving their changes by learning. In general, the brain of insects is divided into three regions: the protocerebrum, deuterocerebrum and tritocerebrum. The protocerebrum is the largest fraction of the brain, including the optical lobes, a pair of lateral-dorsal mushroom bodies, the cerebral bridge and the central body; the deuterocerebrum is partof the brain containing the olfactory antennal centers, and the cell bodies of motor nerves of the antennae muscles and usually form a pair of lateral lobes distinct. Thetritocerebrum is very small in insects, consisting of two small lobes after the deuterocerebrum connected by circum-esophageal commissures to the subesofagean ganglia. Forward, this region connects through nerves, with the oral region and the ganglia of estomogastric nervous system. Despite this apparent simplicity, have systems of spatial orientation and communication very complex and studies have shown that neurotransmitters and receptors are common to those found in vertebrates. According to the developmental stage and the activity performed, the pattern of protein expression is different, reflecting differential gene expression in neurons according to environmental and / or physiological stimuli received, many of these genes similar to those expressed in neurons of vertebrates. This ability to respond physiologically to the varied stimulus, turn on or turn off some genes, stimulating or blocking specific neuronal receptors, makes these insects can be used as models in studies of new drugs possibly neuroactive and also to analyze the effects of neurotoxic substances, as some studies have shown. © 2011 Nova Science Publishers, Inc. All rights reserved.
Keywords: Antennal lobes; Development; Mushroom bodies; Optical lobes; Toxicology